Young Joachim Küttner searching for law in disorder: Detecting waves and rotors through intuitive multi-disciplinarity - Volkert, Hans (2010)
Being in his late twenties, the doctor of law Joachim P. Küttner systematically searched for atmospheric uplift, which could be used for soaring flight, a sport of growing popularity during the 1930s in Germany. Within three years he published no less than six papers dealing with convective up-draughts over Northern Finland as well as in the Balkans, with uplift at the tropopause level during cyclogenesis and with a classification of terms contributing to the quantity of dynamic pressure. However, his broad observational documentation of wave clouds connected with flow across mountain ridges and the experimental description of the vertical motion field during a regional gliding contest at the lee side of the Riesengebirge constituted the landmark paper that made his name known to a wider community. He postulated an intrinsic connection between highly turbulent flow in low levels rotors and often smooth motion in mountain waves aloft. In a companion paper, he also aimed at a theoretical explanation of the available observations. This presentation attempts to recall the essence of Küttner's first surge of publications. In conjunction with a few facts from his family background and his non-standard, highly self-steered academic training in atmospheric physics we arrive at this working hypothesis: "Küttner's early achievements much profited from combining experiences of established law systems and sharp physical observations with the tenacity and perseverance of an active sportsman". It is envisaged that the presentations with foci on later steps in Kuettner's long career can help to corroborate the early findings.